2016
DOI: 10.1038/labinvest.2015.132
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of TRIM27 expression inhibits the proliferation of ovarian cancer cells in vitro and in vivo

Abstract: (tripartite motif-containing 27) was originally identified as a fusion partner with the RET (REarranged during transfection) proto-oncogene and is highly expressed in various tumor cells and tissues. However, the level of expression and function of TRIM27 in ovarian cancer remain unclear. Here we have measured the expression of TRIM27 in normal ovarian and fallopian tube epithelial cells and in ovarian serous carcinoma cells and correlated TRIM27 expression with clinical and pathological parameters. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 32 publications
3
49
0
Order By: Relevance
“…However, whether TRIM27 participates in the progression of lupus nephritis, especially in cell proliferation is still unknown. In this study, we first revealed that the (Ma et al, 2015). Similarly, consistent with these literature, we discovered the overexpression of TRIM27 in the (Gendelman et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, whether TRIM27 participates in the progression of lupus nephritis, especially in cell proliferation is still unknown. In this study, we first revealed that the (Ma et al, 2015). Similarly, consistent with these literature, we discovered the overexpression of TRIM27 in the (Gendelman et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…Several articles had reported that TRIM27 expression played an important role in the proliferation of carcinoma cells. For instance, Ma et al found TRIM27 expression was increased in ovarian serous carcinoma cells and downregulation of TRIM27 expression induced cell cycle arrest (Ma et al, ). Similarly, consistent with these literature, we discovered the overexpression of TRIM27 in the kidneys of patients with LN relating to the proliferation of mesangial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that TRIM27 functioned in an oncogenic role in colorectal cancer and ovarian cancer (Ma et al, 2016). However, the role of TRIM27 in HCC remains unclear.…”
Section: Trim27 Promoted Cell Proliferation Migration and Invasionmentioning
confidence: 99%
“…Recently, it has been reported that TRIM11 is upregulated and play an oncogenic function in glioma (8), lung cancer (9) and colon cancer (10). Several members of TRIM proteins, including TRIM25 (11), TRIM27 (12) and TRIM29 (13), were elevated in ovarian cancer, while TRIM16 expression (14) decreased in ovarian cancer. However, the expression, and functions of TRIM11 in ovarian cancer have been insufficiently characterized.…”
Section: Introductionmentioning
confidence: 99%